WEB Based Design Of Building Materials Marketplace In Percut Sei Tuan District - Yuyun Yusnida Lase; Fildzah Nadiah (Politeknik Negeri Medan, 2021)
Marketplace is an internet-based (web-based) online medium for conducting business activities and transactions between buyers and sellers. One business that can take advantage of marketplace technology is a building shop. Transaction activities at building shops in Percut Sei Tuan District are still done manually. Buyers still have to come to the store to shop or just find out information about products. Existing data in a building shop, such as product data to transaction data, are still recorded in a book. In this study, a web-based application for building materials marketplace in Percut Sei Tuan District was developed using the PHP programming language and MySQL database. The results of this study are expected to assist the building shop in processing existing data, ranging from product data to transaction data, as well as helping customers to shop for building materials without having to come to the store, so as to simplify the transaction process that occurs